Pidana Cambuk dalam Perspektif Keadilan Hukum dan Hak Asasi Manusia di Provinsi Nanggroe Aceh Darussalam - Natangsa Surbakti (Jurnal Hukum IUS QUIA IUSTUM, 2010)
This research discusses the phenomena on Islamic Criminal Law enforcement by applying whipping in the perspective of justice and human rights. Analysis is based on empirical research result in Nangroe Aceh Darussalam using socio-legal approach. Research data includes regulation related to Islamic Law enforcement and dynamic thought of the actors involved in the enforcement of Islamic Law. The research result shows that the competency of sharia court is limited to some criminal conduct regulated in qanun. Competency is limited to the Islam citizen.Key words : Syaria’ court, criminal act, voluntary self submission